2001
DOI: 10.1034/j.1600-0765.2001.360309.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cellular infiltrate, detection of chemokine receptor CCR5 and interleukin‐8 and RANTES chemokines in adult periodontitis

Abstract: Leukocyte migration is essential for immune surveillance of tissues by focusing immune cells to sites of antigenic challenge. The control of leukocyte migration depends on the combined actions of adhesion molecules and a vast array of chemokines and their receptors. The purpose of the present study was to investigate the involvement of Interleukin-8 (IL-8), RANTES, the associated infiltrating cells and expression of CCR5 chemokine receptors in periodontitis; furthermore, the effect of periodontal therapy on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
124
2
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 18 publications
11
124
2
10
Order By: Relevance
“…The chemokine profile elicited from macrophages cultured with P. gingivalis CPS was consistent with that required for recruitment of both neutrophils and mononuclear cells (14,15). The observation that cell-free supernatant fluids from macrophages cultured with P. gingivalis or purified CPS facilitated inflammatory cell migration demonstrated that the chemokine response of inflammatory cells to this antigen functions as a gradient that is sensed by inflammatory cells, allowing for naïve inflammatory cell migration.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The chemokine profile elicited from macrophages cultured with P. gingivalis CPS was consistent with that required for recruitment of both neutrophils and mononuclear cells (14,15). The observation that cell-free supernatant fluids from macrophages cultured with P. gingivalis or purified CPS facilitated inflammatory cell migration demonstrated that the chemokine response of inflammatory cells to this antigen functions as a gradient that is sensed by inflammatory cells, allowing for naïve inflammatory cell migration.…”
Section: Discussionmentioning
confidence: 60%
“…A variety of cell culture models show that epithelial cells, fibroblasts, and mononuclear cells and PMNs express chemokines when cultured with P. gingivalis (26,28,30,54). Indeed, increased expression of the chemokines MCP-1, MIP-1␣, and RANTES has been reported for human and murine cells cultured with P. gingivalis (28,55), just as MCP-1, RANTES, and IL-8 are found at elevated levels in the gingival crevicular fluid of diseased periodontal tissue (11,14,22). Various studies have focused on the contributions of specific antigens from P. gingivalis to inflammatory responses to the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, los resultados discrepan con otros estudios (19)(20)(21) en cuanto a los niveles reportados para los sitios control, en los que se observó una cuantificación hasta 50% mayor en los niveles de CCL5.…”
Section: Discussionunclassified
“…Las cuantificaciones obtenidas en el presente estudio para sitios enfermos fueron menores en pacientes diabéticos y no diabéticos, variación inherente a las diferencias en el diseño de los estudios; el curso de la enfermedad fue más grave en su grupo de pacientes muestra, determinaron sitios sanos y enfermos en el mismo paciente comprometido con PC, y los sitios a muestrear se determinaron después de un periodo de 2 meses de seguimiento. El incremento en los niveles de CCL5 en pacientes con periodontitis, en acuerdo con los resultados del presente reporte, también ha sido descrito por otros autores (13,19,20,23).…”
Section: Discussionunclassified
“…On the other hand, the absence of CCL3 does not affect the development of experimental PD in mice, probably due to the presence of homologous chemokines CCL4 and CCL5 which share the receptors CCR1 and CCR5 with CCL3 and present a similar kinetics of expression than CCL3 (Repeke et al, 2010). Regulated upon Activation Normal T-cell Expressed and Secreted (RANTES/CCL5) is found in greater levels in active periodontal lesions compared to inactive sites (Gamonal et al, 2001, Gemmell et al, 2001) and it chemoattracts lymphocytes and monocytes as well as other cell types (Koch et al, 2005, Schall et al, 1990. The involvement of CCL5 in periodontal bone resorption is supported by findings that it binds to CCR1 and/or CCR5 (Garlet et al, 2003), inducing chemotaxis and the formation of osteoclasts in vitro (Yu et al, 2004).…”
Section: Chemokines As Determinants Of Host Response Naturementioning
confidence: 99%